2018
DOI: 10.1111/aji.12991
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, autoimmunity and recurrent pregnancy loss: More than an association

Abstract: Recurrent pregnancy loss (RPL) affects close to 1% of couples; however, the etiology is known in only about 50% of the cases. Recent studies show that autoimmune dysregulation is a probable cause of RPL, which in some cases may be overlooked. In order for a pregnancy to proceed to term, early modulation of immunologic response is required to induce tolerance to the semi-allogenic fetus. Certain subsets of both the innate and adaptive immune responses play a role in the induction of fetomaternal tolerance. A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 129 publications
(251 reference statements)
0
29
0
3
Order By: Relevance
“…An increase in T helper 1 and T helper 17 cell activity may increase risk, whereas promotion of T helper 2 cell populations may infer protection and vitamin D may play a direct role here. 71 Recurrent pregnancy loss affects 1%–2% of reproductive women and studies show an association with vitamin D deficiency. 72 Vitamin D level, therefore, may be an important clinical consideration, particularly as recurrent pregnancy loss is often unexplained.…”
Section: Vitamin Dmentioning
confidence: 99%
“…An increase in T helper 1 and T helper 17 cell activity may increase risk, whereas promotion of T helper 2 cell populations may infer protection and vitamin D may play a direct role here. 71 Recurrent pregnancy loss affects 1%–2% of reproductive women and studies show an association with vitamin D deficiency. 72 Vitamin D level, therefore, may be an important clinical consideration, particularly as recurrent pregnancy loss is often unexplained.…”
Section: Vitamin Dmentioning
confidence: 99%
“…Vitamin D RCTs specifically designed to assess outcomes of ART are, however, still missing. Interestingly, one meta-analysis documented that early spontaneous pregnancy loss was significantly increased in women with serum 25(OH)D concentrations below 50 nmol/L compared to those with higher 25(OH)D levels (relative risk (RR): 2.24; 95% CI: 1.15 to 4.37) [ 54 , 55 , 56 ]. In line with this, a study in 1191 women with previous pregnancy losses showed that women with serum 25(OH)D concentrations ≥75 nmol/L preconception were more likely to achieve clinical pregnancy (adjusted RR: 1.10; 95% CI: 1.01 to 1.20) and livebirth (RR: 1.15; 95% CI: 1.02 to 1.19) compared to those with lower serum 25(OH)D concentrations [ 57 , 58 ].…”
Section: Fertilitymentioning
confidence: 99%
“…Vitamin D is a secosteroid hormone regulating the expression of almost 900 genes [1] and it is involved in the regulation of calcium and phosphate metabolism, immune response and brain development [2, 3]. Low blood Vitamin D levels have been reported in patients affected by infectious diseases, including those caused by parasites [4].…”
Section: Introductionmentioning
confidence: 99%